SISTEM INFORMASI SERVIS KOMPUTER BERBASIS WEB STUDI KASUS DATACOM - Muhammad Ichsan; Fitria Fitria (Phasti: Jurnal Teknik Informatika Politeknik Hasnur, 2021)
Datacom is a private company engaged in the sale and repair of computers. Services in the datacom must be done properly and correctly to facilitate and speed up the flow of services, a computer data processing information system is very appropriate to simplify services on the datacom. This study aims to produce a computer service information system in Datacom, this system is built based on a website using the Codeigniter Framework and will be developed using the Waterfall method. Testing on this system using Blackbox Testing results in the system being able to check the status of computer service, can print service data, and can print data service reports per month.